Comparative study on secondary metabolites from different citrus varieties in the production area of Zhejiang - Lin, Mei; Xu, Chengnan; Gao, Xueying; Zhang, Weiqing; Yao, Zhoulin; Wang, Tianyu; Feng, Xianju; Wang, Yue (Frontiers in Nutrition, 2023)
To investigate the distribution pattern of bioactive components and their correlations between citrus varieties, we thoroughly analyzed secondary metabolites (including flavonoids, phenolic acids, carotenoids, and limonoids) in the peel and pulp of 11 citrus varieties from the production area of Zhejiang. Citrus peels accumulated metabolites far more than the pulp, and the accumulation varied significantly between species. Flavonoids were the most abundant compounds, followed by phenolic acids, with carotenoids and limonoids being far less abundant than the first two, but limonoids were more abundant than carotenoids. Hesperidin was the main flavonoid in most varieties, but cocktail grapefruit and Changshanhuyou contained naringin, with Ponkan having the most abundant polymethoxylated flavones (PMFs). The major components of phenolic acids, carotenoids, and limonoids were ferulic acid, β-cryptoxanthin, and limonin, respectively. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) indicated that these components were mostly correlated with each other, and these citrus varieties could be categorized into four groups by pulp and three groups by peel. The obtained results filled the data gap for secondary metabolites from local citrus and could provide data references for citrus resource utilization, selection and breeding of superior varieties, and other research.